Existence, uniqueness, and dependence on a parameter of solutions of differential-functional equations with ordinary and partial derivatives - Bigun, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For a system of quasilinear hyperbolic equations with a system of differential equations with lag, we prove theorems on the existence and uniqueness of a solution of the Cauchy problem and its continuous dependence on the initial conditions.